2004
DOI: 10.1002/ajp.20016
|View full text |Cite
|
Sign up to set email alerts
|

Paleoenvironmental basis of cognitive evolution in great apes

Abstract: A bias favoring tree-dominated habitats and ripe-fruit frugivory has persisted in great ape evolution since the early Miocene. This bias is indicated by fossil ape paleoenvironments, molar morphology, dental microwear, the geographic pattern of extinctions, and extant apes' reliance on wooded settings. The ephemeral aspect of high-quality fruit has placed a premium on cognitive and social means of finding and defending food sources, and appears related to great apes' affinity since the Miocene for wooded, frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 68 publications
1
48
0
1
Order By: Relevance
“…We propose that large-brained foragers that need a reliable and steady intake of high-energy nutrition to maintain their large and costly brains (6,11) could gain a clear evolutionary advantage by using flexible planning that reduces indirect interspecific competition. This attribute may have been particularly important for hominoids that specialized on stationary, energy-rich, and highly ephemeral food, such as ripe fruit (14,17,24), abandoned meat carcasses, or aquatic fauna trapped in receding waters (56). The proposed benefit of flexible planning skills, especially for hominids living in highly seasonal habitats like savannah, strongly encourages a more detailed focus on the temporal aspect of ecological complexity than has been done to date (1,6), and a resumed investigation of its role in theories of primate and, in particular, hominid brain size evolution (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that large-brained foragers that need a reliable and steady intake of high-energy nutrition to maintain their large and costly brains (6,11) could gain a clear evolutionary advantage by using flexible planning that reduces indirect interspecific competition. This attribute may have been particularly important for hominoids that specialized on stationary, energy-rich, and highly ephemeral food, such as ripe fruit (14,17,24), abandoned meat carcasses, or aquatic fauna trapped in receding waters (56). The proposed benefit of flexible planning skills, especially for hominids living in highly seasonal habitats like savannah, strongly encourages a more detailed focus on the temporal aspect of ecological complexity than has been done to date (1,6), and a resumed investigation of its role in theories of primate and, in particular, hominid brain size evolution (11).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated whether a ripe-fruit specialist, the chimpanzee (24), uses prospective cognition to arrive earlier at breakfast sites with ephemeral and highly sought-after fruits (in particular figs and small fruits) than those with less ephemeral fruit that can be more predictably obtained throughout the entire day. To accomplish this, we recorded and analyzed (i) the nest (sleeping site) departure times and (ii) nest positioning relative to breakfast-site locations of five adult female chimpanzee all with young offspring (<7 y) during three fruit-scarce periods in the Taï National Park, Ivory Coast (25,26).…”
Section: Significancementioning
confidence: 99%
“…These traits tended to be found in those birds with a large relatively sized brain, an omnivorous diet, a complex social system and which live in a harsh, changeable environment: traits which are shared with mammals that have been suggested to be the most intelligent. Indeed, Godfrey-Smith (1996), Sterelny (2003) and Potts (2004) have suggested that such environmental complexity presented numerous ecological problems for our hominid ancestors which could only be solved by the evolution of flexible forms of innovative behaviour.…”
Section: The Avian Social Brain?mentioning
confidence: 99%
“…For example, Byrne (1999) suggests that ape planning and cultural learning abilities allow apes to gain access to novel foods. Potts (2004) proposes that habitat instability about 9.5 mya increased the diYculty of surviving on a ripe fruit diet and selected for cognitive and social means of Wnding food and is responsible for the higher intelligence of apes.…”
Section: The Papers In This Issuementioning
confidence: 99%